Neurological risks of COVID-19 in women: the complex immunology underpinning sex differences - Gu, Jienan; Zhang, Jiale; Liu, Qianhui; Xu, Shijie (Frontiers in Immunology, 2023)
The COVID-19 pandemic has uncovered many mysteries about SARS-CoV-2, including its potential to trigger abnormal autoimmune responses. Emerging evidence suggests women may face higher risks from COVID-induced autoimmunity manifesting as persistent neurological symptoms. Elucidating the mechanisms underlying this female susceptibility is now imperative. We synthesize key insights from existing studies on how COVID-19 infection can lead to immune tolerance loss, enabling autoreactive antibodies and lymphocyte production. These antibodies and lymphocytes infiltrate the central nervous system. Female sex hormones like estrogen and X-chromosome mediated effects likely contribute to dysregulated humoral immunity and cytokine profiles among women, increasing their predisposition. COVID-19 may also disrupt the delicate immunological balance of the female microbiome. These perturbations precipitate damage to neural damage through mechanisms like demyelination, neuroinflammation, and neurodegeneration – consistent with the observed neurological sequelae in women. An intentional focus on elucidating sex differences in COVID-19 pathogenesis is now needed to inform prognosis assessments and tailored interventions for female patients. From clinical monitoring to evaluating emerging immunomodulatory therapies, a nuanced women-centered approach considering the hormonal status and immunobiology will be vital to ensure equitable outcomes. Overall, deeper insights into the apparent female specificity of COVID-induced autoimmunity will accelerate the development of solutions mitigating associated neurological harm.